2020
DOI: 10.1016/j.dib.2019.104845
|View full text |Cite
|
Sign up to set email alerts
|

Data on the relationship between caffeine addiction and stress among Lebanese medical students in Lebanon

Abstract: Stress continues to be a global burden. It may be thought of as necessary to human thriving; however, challenging and unfavorable functioning may take place when many significant stressors are imposed repetitively or concurrently without resolve. Research suggests that medical students perceive higher levels of stress than students in other health-related disciplines [1–3]. Since caffeine is a psychoactive substance that stimulates the central nervous system, medical students use to consume it more than other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 9 publications
2
12
0
3
Order By: Relevance
“…Caffeine consumption was popular among our study sample, with 92.2% indicating that they use a certain caffeinated product, most commonly coffee, soft drinks, and tea. This data is homogeneous with a study done on different university students in Lebanon indicating that 97% of 800 students use caffeine products [4]. Despite the literature showing a positive association between caffeine consumption and both aerobic and anaerobic activities [2], our results showed the absence of signi cant association between aerobic exercises and the three factors for the caffeine consumption variable: (1) caffeine as a physical performance enhancer, (2) caffeine as work durability enhancer and (3) caffeine as a productivity enhancer.…”
Section: Discussionmentioning
confidence: 46%
See 4 more Smart Citations
“…Caffeine consumption was popular among our study sample, with 92.2% indicating that they use a certain caffeinated product, most commonly coffee, soft drinks, and tea. This data is homogeneous with a study done on different university students in Lebanon indicating that 97% of 800 students use caffeine products [4]. Despite the literature showing a positive association between caffeine consumption and both aerobic and anaerobic activities [2], our results showed the absence of signi cant association between aerobic exercises and the three factors for the caffeine consumption variable: (1) caffeine as a physical performance enhancer, (2) caffeine as work durability enhancer and (3) caffeine as a productivity enhancer.…”
Section: Discussionmentioning
confidence: 46%
“…Our ndings are convergent with a double-blind, placebo-controlled randomized cross over study on anaerobic activities. Madden et al revealed that perceived effort is greater in the caffeine group compared to the placebo [9] suggesting that caffeine could increase overall physical performance in anaerobic activities. Moreover, McDaniel et al (2010) showed a 4.2 seconds enhancement in anaerobic activities in the caffeine group compared to placebo [2].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations